Analysis of the Creative Thinking Ability of Students SMA N 1 Pecangaan Jepara on Environmental Change Material - Utami, Retna; Marianti, Aditya; Susanti, R. (Journal of Biology Education, 2018)
Creative thinking is an ability of creating a new thought as a result from combination of previous knowledge. It is needed to be developed in the 21st century because it is importance in work world. This study aims to analyze the studentsâ creative thinking of SMA N 1 Pecangaan on environmental material. The research used observational method. Population is whole students of tenth grade of SMA N 1 Pecangaan. The samples used purposive samplings were X MIA 1, X MIA 2 and X MIA 4 with total number 116 students. The studentsâ creative thinking was tested by essay test and instrument non-test which is scoring rubric of writing article about environment problems. The result showed that studentsâ creative thinking of SMA N 1 Pecangaan in answering question is 14.7% very creative, 31% creative, 20.7% creative enough and 33.6% less creative. The studentsâ ability in writing article showed 0% very creative, 16.4% creative, 30% creative enough, 49.1% less creative and 4.3% not creative. The research concluded that the creative thinking ability of students SMA N 1 Pecangaan is low. The highest aspects of creative thinking that is reached by students are originality and fluency, while the lowest is elaboration.